PENGARUH SERVICESCAPE DAN HARGA TERHADAP KEPUASAN PENGUNJUNG DI MUSEUM ANGKUT MOVIE STAR STUDIO KOTA BATU - Wilujeng, Sri (IQTISHODUNA, 2017)
Abstract: The purpose of this research is to find out the influence of servicescape and price to the satisfactionof visitors. This research was conducted at Museum Angkut Movie Star Studio Kota Wisata Batu. Samples ofthis study are 120 respondents, through purposive sampling method. Data collection was done throughobservation and questionnaires. Based on the analysis multiple linear regression research shown thatservicescape and prices simultaneous effect on satisfaction of visitors. Servicescape and prices partial effecton satisfaction of visitors. Servicescape predominantly affect the satisfaction of visitors.